2010
DOI: 10.1021/jp910685z
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Effect of (001) TiO2Anatase Support on V2O5

Abstract: The effect of (001) TiO 2 anatase support on the electronic and catalytic properties of a V 2 O 5 monolayer is analyzed using density functional theory (DFT). The catalyst is represented by both clusters and periodic slabs. Using two experimentally relevant models of monolayer V 2 O 5 /TiO 2 (anatase) catalyst, both weak and strong interactions between a V 2 O 5 monolayer and the TiO 2 support have been investigated. In the first model, where a crystallographic (001) V 2 O 5 layer is placed on top of the (001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 65 publications
3
24
0
Order By: Relevance
“…These results from DFT may aid in the design of improved catalysts for mercury oxidation while simultaneously maintaining optimal performance for NO x reduction. The TiO 2 (001) surface has been studied previously, 16,25,30,72 and is shown in Figure 9. It is composed of five-coordinated Ti atoms bonded to two O atoms along the (001) direction and to three O atoms in the (010) direction.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…These results from DFT may aid in the design of improved catalysts for mercury oxidation while simultaneously maintaining optimal performance for NO x reduction. The TiO 2 (001) surface has been studied previously, 16,25,30,72 and is shown in Figure 9. It is composed of five-coordinated Ti atoms bonded to two O atoms along the (001) direction and to three O atoms in the (010) direction.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Two approaches to construct models of supported vanadium oxide ML structures are reported in the literature: (i) substitution of metal atoms of the support with vanadium atoms, for example in anatase TiO2(001), 37 α-Al2O3(0001), 38 κ-Al2O3(001) 39 and Al2O3/NiAl(110), 40 or (ii) deposition of vanadium oxide layers cut from bulk phases on the support, e.g. V2O3 on…”
Section: Introductionmentioning
confidence: 99%
“…Al2O3/NiAl(110) 40 and V2O5 on anatase TiO2(001). 37,[41][42] Thus, the monolayers are typically structurally similar either to the support or the corresponding bulk vanadium oxide. This is different with monolayers on CeO2(111).…”
Section: Introductionmentioning
confidence: 99%
“…25,44,45 Accordingly, theoretical studies of surface VO x species have focused to date on understanding the nature of the VO x -support interactions, the molecular structure-reactivity relationships for propane ODH, and especially the mechanism of the initial C-H bond activation step. 47 Extensive experimental and theoretical evidence has been gathered in support of the basic tetrahedral structure of an isolated VO x species where a V 51 cation forms a short double bond to terminal oxygen and 3 bonds to oxide support via bridging oxygens. [48][49][50][51] Cheng et al 52 has studied conversion of propane to propanol by the anatase TiO 2 -supported VO x monomers and dimers using B3LYP.…”
Section: Supported Vanadia Catalystsmentioning
confidence: 99%
“…Therefore, the high coverage of vanadia on the support surface is beneficial for the selectivity of supported vanadia to propene. Alexopoulos et al 37,47 have performed extensive DFT calculations of propane oxidation over anatase TiO 2 -suppoted V 2 O 5 (001) surface employing cluster and periodic slab models. They found that the anatase support enhances the Lewis acidity of the vanadia monolayer and the catalytic activity of the vanadyl oxygen leading to lower H binding energy on the vanadyl site.…”
Section: Supported Vanadia Catalystsmentioning
confidence: 99%